PENEMUAN SEBUAH CANDI BATA DI DAERAH PANTURA JAWA TENGAH - Rita Istari (Balai Arkeologi Yogyakarta, 2012)
The discovery of Kayen Temple in Pati Regency adds the numbers of brick-made temples in Central Java. Balai Arkeologi Yogyakarta conducted previously, a research in areas near Borobudur on assumption that these areas were the cultural and political center of ancient civilization and a fact that most temples are located near Borobudur Temple within 15 kilometers radius. Those temples were either made from andesites or bricks. Temples made from bricks are often discovered in small size, they show that bricks were one of popular building materials that used for temples other than andesites. Kayen Temple is considered as a rare discovery of brick-made temple in the Northern Coast of Central Java. Pati Regency profoundly known as destination for pilgrimage because of its Islamic Heritage also has many destination for Classic Hinduism Heritage